Visual literacy in STEAM content on the Instagram account @idemain_jab: Literasi visual dalam konten STEAM akun instagram @idemain_jab - Wulandari, Dwi; Zahra, Mutiah Az; Maulana, Afnan Barkah N. G. A. A. S.; Firdaus, Zulfan Al; Saputra, Miftahul Hilda (Universitas Negeri Yogyakarta, 2025)
Social media has become an essential medium for enhancing literacy. This study examines the role of visual literacy in STEAM (Science, Technology, Engineering, Arts, Mathematics) content on the Instagram account @idemain_jab through a netnographic approach. The analysis reveals that visual elements such as contrasting colours, simple symbols, patterns, and animations are employed to simplify complex STEAM concepts. Each post combines visual aesthetics with simple educational narratives and expressive emojis to enhance understanding. Emerging themes include experimentation, child independence, art integration, visual effects, educational infographics, cultural symbolism, and safety. Active user engagement—through comments, likes, and reposts—demonstrates the effectiveness of visual literacy in fostering participation and knowledge exchange. Visual literacy not only improves comprehension and learning motivation but also strengthens community identity while fostering creativity, critical thinking, and collaborative skills. _______________________________________________________________________________ Media sosial kini menjadi sarana penting dalam meningkatkan literasi. Penelitian ini mengkaji peran literasi visual dalam konten STEAM (Science, Technology, Engineering, Arts, Mathematics) pada akun Instagram @idemain_jab menggunakan pendekatan netnografi. Analisis menunjukkan bahwa elemen visual seperti warna kontras, simbol sederhana, pola, dan animasi digunakan untuk menyederhanakan konsep STEAM yang kompleks. Setiap unggahan memadukan estetika visual dengan narasi edukatif berbahasa sederhana dan emoji ekspresif guna memperkuat pemahaman. Tema yang diangkat mencakup eksperimen, kemandirian anak, integrasi seni, efek visual, infografis edukatif, simbolisme budaya, dan keamanan. Interaksi aktif pengguna, seperti komentar dan repost, menunjukkan efektivitas visual dalam membangun partisipasi. Literasi visual tidak hanya meningkatkan pemahaman dan motivasi belajar, tetapi juga memperkuat identitas komunitas serta mengembangkan kreativitas, berpikir kritis, dan kolaboratif.